Blood glucose lowering effects of lepidium meyenii (maca), marine collagen peptides, and Blackbelt® coffee in rat model of diabetes mellitus - Ismawi, Hidayatul Radziah; Othman, Najwa Hanim; Mohd. Zainudin, Maizura; Abd. Fuaat, Azliana (2023)
BACKGROUND AND OBJECTIVES: The number of cardiometabolic disease Type 2 diabetes mellitus (T2DM) patients are expected to increase to 552 million people worldwide by 2030. Current treatment options potential therapeutic benefits of natural products such as Lepidium meyenii (Maca) and marine collagen peptides (MCP), as well as Blackbelt® coffee on T2DM by using streptozocin induced DM rat model. METHODS: 36 male Sprague Dawley rats were fed high-fat diet for 3 weeks (60% commercial feed, 20% ghee fat, 20% sucrose) and given low dose streptozocin injection (40 mg/kg) intraperitoneally to achieve fasting blood glucose (FBG) >15 mmol/mL. The rats were divided into negative control, metformin (200 mg/kg metformin), maca (13 mg/kg maca), MCP (264 mg/kg MCP), maca/MCP (Blackbelt® formulation) and Blackbelt® (132 g/kg of Blackbelt®) and treated for 28 days. RESULTS: Rat body weight and FBG levels were measured at 0, 2 and 4 weeks. Maca/MCP group showed highest increase in weight (95g) and maca group showed least weight increase (59g). All increase in weight was not statistically significant compared to control. Metformin (7.34 ± 1.6 mmol/mL), maca (10.9 ± 2.9 mmol/mL), MCP (10.1 ± 4.4 mmol/mL) and Blackbelt® (11.33 ± 2.7 mmol/mL) was significantly lower than control group (16.4 ± 4.6 mmol/mL) at week 4 of treatment. CONCLUSIONS: Reduction in blood glucose by maca, MCP and Blackbelt® coffee is comparable but not superior to metformin in T2DM rat model without affecting body weight.